ECO-PEDAGOGY FOR SUSTAINABLE CHARACTER EDUCATION IN ELEMENTARY SCHOOLS: A CRITICAL REVIEW IN THE CONTEXT OF PHILOSOPHY OF SCIENCE - Heni Yuliani; Yusuf Tri Herlambang (Jurnal Cakrawala Pendas, 2026)
Global environmental crises such as climate change, pollution, and biodiversity loss demand a paradigm shift in education that focuses not only on cognitive aspects but also on character building and ecological awareness. Primary education plays a strategic role in instilling sustainability values from an early age through an integrative approach. This study aims to analyze the role of philosophy of science in the development of eco-pedagogy as a foundation for strengthening sustainable character education in elementary schools. The research uses a literature review method with the following stages: (1) searching for scientific articles through relevant national and international databases; (2) selecting sources based on the suitability of the themes of philosophy of science, ecopedagogy, and character education; and (3) conceptual analysis and thematic synthesis. The results of the study show that ontologically, ecopedagogy views humans as an integral part of the ecosystem; epistemologically, environmental knowledge is constructed through reflective, contextual, and critical learning; and axiologically, education is directed at forming moral responsibility and concern for the environment. The integration of philosophy of science in ecopedagogy strengthens the integration between knowledge, values, and ecological actions of students. In practical terms, elementary school teachers can design environment-based thematic learning, use reflective methods and contextual projects, and instill environmental ethics values in daily learning activities. Thus, eco-pedagogy based on the philosophy of science contributes significantly to shaping the character of students to be sustainable and ecologically aware.